RESPONSIVITAS PEMERINTAH KOTA JAMBI DALAM PENERAPAN APLIKASI SIKESAL DITINJAU DARI KONSEP PEMERINTAHAN DIGITAL - Vina Zuela, Erika; Yusri Maulana, Rio; Syufradian Putra, Dinda (Prodi Ilmu Pemerintahan FISIP UNIBBA, 2025)
The government, as the primary provider of public services, faces challenges to continuously adapt to technological advancements to enhance the efficiency, accessibility, and responsiveness of services to the community. In the context of digital governance, responsiveness is a key element in ensuring public services meet community needs in a timely and efficient manner. One concrete effort to optimize technology implementation is through the SIKESAL application (Sistem Informasi Keluhan dan Aspirasi Layanan). This application was developed by the Jambi City Government as part of the implementation of the smart city concept in Jambi City, functioning as a platform for public complaints. This study analyzes the responsiveness of the Jambi City Government in managing the SIKESAL application and evaluates its effectiveness in improving the quality of public services. Using a qualitative descriptive method, the study gathers primary and secondary data through observations, interviews, and documentation. The results reveal that the SIKESAL application has significant potential as a medium for public complaints. The application is equipped with key features such as real-time reporting, location integration, and photo uploads. However, its implementation faces several challenges, including low adoption rates among the public. Factors contributing to this low adoption include insufficient public outreach about the application’s usage and benefits, as well as the existence of stigma or negative perceptions toward the application as a reporting tool. This study recommends enhancing public communication strategies, community education, andimproving application features to ensure broader adoption and improve public service quality.